1995
DOI: 10.1111/j.1476-5381.1995.tb13222.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT3 receptor antagonism by anpirtoline, a mixed 5‐HT1 receptor agonist/5‐HT3 receptor antagonist

Abstract: 1 The aim of this study was to provide evidence that anpirtoline, which is an agonist at 5-HTIB and 5-HT,D receptors and also displays submicromolar affinity for 5-HTlA recognition sites, in addition, acts as an antagonist at 5-HT3 receptors. 2 In radioligand binding studies on rat brain cortical membranes, anpirtoline inhibited specific binding of [3H]-(S)-zacopride to 5-HT3 receptor recognition sites (pKi: 7.53).3 In NIE-115 neuroblastoma cells in which ['4C]-guanidinium was used as a tool to measure cation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In comparison, anpirtoline only shows a five-fold preference for the rat 5-HT 1B receptor (K i ¼ 28 nM) vs the rat 5-HT 1A (K i ¼ 150 nM) and a 50-fold preference vs the 5-HT 2 (K i ¼ 1.49 mM) receptor (Schlicker et al, 1992). Furthermore, anpirtoline has been shown to act as a 5-HT 3 antagonist in both binding assays (pK i ¼ 7.53) and 5-HT IB receptors and learning M Å hlander-Lüttgen et al behavioral studies (Gothert et al, 1995). This implies that anpirtoline, at least at high doses, could stimulate the 5-HT 1A receptor, evidenced by the observation that animals treated with anpirtoline displayed parts of the serotonin syndrome (flat body posture) during the WM task (see Results section).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In comparison, anpirtoline only shows a five-fold preference for the rat 5-HT 1B receptor (K i ¼ 28 nM) vs the rat 5-HT 1A (K i ¼ 150 nM) and a 50-fold preference vs the 5-HT 2 (K i ¼ 1.49 mM) receptor (Schlicker et al, 1992). Furthermore, anpirtoline has been shown to act as a 5-HT 3 antagonist in both binding assays (pK i ¼ 7.53) and 5-HT IB receptors and learning M Å hlander-Lüttgen et al behavioral studies (Gothert et al, 1995). This implies that anpirtoline, at least at high doses, could stimulate the 5-HT 1A receptor, evidenced by the observation that animals treated with anpirtoline displayed parts of the serotonin syndrome (flat body posture) during the WM task (see Results section).…”
Section: Discussionmentioning
confidence: 97%
“…NAS-181 has been demonstrated to enhance 5-HT metabolism in the rat brain in a dose-dependent manner (0.1-20 mg/kg, s.c.), with maximal effects 60 min after the injection (Stenfors et al, 2000). The effects of NAS-181 on performance in the WM and PA tasks as well as the ability of the compound to block or attenuate the effects of a nonselective 5-HT 1B agonist, anpirtoline were investigated (Gothert et al, 1995;Schlicker et al, 1992;Swedberg et al, 1992). The serotonergic and cholinergic systems appear to interact in various aspects of learning and memory (Steckler and Sahgal, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Polymeropoulos and Kutscher [19] found that some centrally acting analgesics with different mode of activity, including epibatidine and anpirtoline [20][21][22][23] , have similar energetically low-lying conformations. Antinociceptive activity of epibatidine is caused by its strong agonistic activity on neuronal nicotinic receptors [24] while it has no effect on both serotonin type l and muscarinic receptors.…”
Section: Resultsmentioning
confidence: 99%
“…It was found to be a mixed 5-HT1 receptor agonist/5-HT3 receptor antagonist. The 5-HT1B agonistic activity is expected to be its principal mode of action [4,5] . In spite of its pronounced analgesic activity, the drug has not been introduced into the market, probably due to unspecified side effects.…”
Section: Introductionmentioning
confidence: 99%